Mechanical characterization and impact damage assessment of Al/SiC functionally graded coating under elevated temperatures - D. Muniraj; S. Vignesh; V. M. Sreehari (Scientific Reports, 2024)
Abstract Functionally graded materials are a class of composite materials that finds widespread use in aerospace, defense and automobile applications due to their tailored material properties for the specific need. In the present research, impact dynamics and the damage behavior of functionally graded plasma spray coating (FGPS) on an aluminium 6061-T6 substrate under high velocity impact at various temperatures were studied. The FGPS coating consists of four layers having various proportions of Al and SiC (50/50, 40/60, 30/70 and 20/80 weight percentages) and the coating thickness was measured to be 232.8 μm. Experiments were carried out at 260 J of impact energy on the FGPS samples at various temperatures using a single-stage gas gun along with the thermal setup. A finite element model was developed with the Johnson-Cook damage model and piecewise linear plasticity material model, along with suitable contact algorithms. Impact simulations at various temperatures reveal that the stiffness reduction at higher temperatures results in decreased peak contact force, decreased rebound velocity and increased central deflection. The molten splats observed through the micro-morphological study have spread several micrometers, which indicates excellent bonding between the particles and the porosity content was found to be 1.35%. The research findings on the impact dynamics and damage behavior of FGPS can significantly improve material design for a wide range of applications.